Enhanced refractive index sensitivity for anomalous reflection of gold to improve performance of bio-molecular detection - Amir Hamzah, Amir Syahir; Kajikawa, Kotaro; Mihara, Hisakazu (Elsevier, 2014)
Biomolecular detection techniques based on the anomalous reflection (AR) of gold may allow the development of new label-free methods for the study of biomolecular interactions. Such methods measure reflectivity at a normal incidence angle and thus are well suited to practical applications in biochip format. Our calculations predicted that the use of an AR substrate with an optimized dielectric constant would improve the sensitivity of this technique compared to that obtained with standard gold substrates. We subsequently fabricated Au–Ag alloy substrates and their corresponding oxide composites (Au–Ag2O) to experimentally confirm the predicted higher sensitivity. The dielectric constants of these new substrates were found to result in the enhanced levels of sensitivity predicted by calculations.